I.i.13. Correspondence - PEN. Dublin Centre; Lavin, Mary, 1912-1996.; Guinness, Bryan, 1905-1992; Ó Néill, Séamus; Clarke, Desmond (1975)
Mainly to/from Desmond Clarke, Dublin P.E.N Honorary Secretary. Content is predominantly administrative in nature. Also includes resignation letters of Séamus Ó Néill.
Keywords: PEN. -- Dublin Centre; PEN. -- Belfast Centre; PEN (Organization); English literature -- Irish authors -- 20th century